ZnO Nanoparticles Applied to Bioimaging and Drug Delivery - Xiong, Huan-Ming (Advanced materials (Weinheim), 2013)
The last decade has seen significant achievements in biomedical diagnosis and therapy at the levels of cells and molecules. Nanoparticles with luminescent or magnetic properties are used as detection probes and drug carriers, both in vitro and in vivo. ZnO nanoparticles, due to their good biocompatibility and low cost, have shown promising potential in bioimaging and drug delivery. The recent exciting progress on the biomedical applications of ZnO‐based nanomaterials is reviewed here, along with discussions on the advantages and limitations of these advanced materials and suggestions for improving methods. ZnO nanoparticles can be used in bioimaging probes and drug carriers. The major highlights of recent progress in these applications are reviewed. Multifunctional probes can be synthesized for curing animal tumors, which contain luminescent ZnO quantum dots. ZnO nanoparticles can also be used to produce probes with magnetic elements for anticancer drugs or with specific groups for identifying tumors, allowing the nanoparticle to be guided to cancerous cells. Under UV light irradiation, ZnO nanoparticles can produce plenty of reactive oxygen species which help destroy cancer cells.